Web-based lecture technologies and learning and teaching: a study of change in four Australian universities - M. Gosper; M. Mcneill; R. Phillips; G. Preston; K. Woo; D. Green (Association for Learning Technology, 2010)
The uptake of web-based lecture technologies for recording and delivering live lectures has increased markedly in recent years. Students have responded positively, and for many their use has transformed learning – freeing them up from rigid timetables by providing choice in lecture attendance and supporting learning by extending the lecture experience and enabling them to revisit key concepts and ideas in their own time. Less transformational has been the impact on teaching. Although changing attendance patterns and disquiet about the quality of learning are of concern to many, lecturers have largely responded by simply modifying lectures. For most, the challenges of catering for the learning needs of a cohort with variable lecture attendance have not been addressed at a whole of the curriculum level. The technologies have been added on, rather than integrated into the curriculum. This paper will review the changes taking place in learning and teaching, explore the reluctance to embrace more wholesale change to the curriculum, and discuss the implications for institutions in the face of ongoing change.